1999
DOI: 10.1182/blood.v93.1.293
|View full text |Cite
|
Sign up to set email alerts
|

ETV6-AML1 Translocation Breakpoints Cluster Near a Purine/Pyrimidine Repeat Region in the ETV6 Gene

Abstract: The t(12;21)(p13;q22) translocation, fusing the ETV6 andAML1 genes, is the most frequent chromosomal translocation associated with pediatric B-cell precursor acute lymphoblastic leukemia. Although the genomic organization of the ETV6 gene and a breakpoint cluster region (bcr) in ETV6 intron 5 has been described, mapping of AML1 breakpoints has been hampered because of the large, hitherto unknown size of AML1 intron 1. Here, we report the mapping of the AML1 gene between exons 1 and 3, cloning of ETV6-AML1 brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Illegitimate recombination events at cryptic RSS motifs have been implicated in several recurrent chromosomal abnormalities in lymphoid malignancies, such as translocations and deletions. For example, both ETV6-RUNX1 and BCR-ABL1 translocations have been suggested to arise from mistargeting of RAG proteins that facilitate RAG-mediated transposition or at least create one of the initiating lesions in the form of nicks [29] [31] . This mistargeting of RAG proteins may occur as a rare spontaneous event during lymphocyte differentiation, but may also result from increased or prolonged RAG activity in leukemic lymphoid blasts.…”
Section: Discussionmentioning
confidence: 99%
“…Illegitimate recombination events at cryptic RSS motifs have been implicated in several recurrent chromosomal abnormalities in lymphoid malignancies, such as translocations and deletions. For example, both ETV6-RUNX1 and BCR-ABL1 translocations have been suggested to arise from mistargeting of RAG proteins that facilitate RAG-mediated transposition or at least create one of the initiating lesions in the form of nicks [29] [31] . This mistargeting of RAG proteins may occur as a rare spontaneous event during lymphocyte differentiation, but may also result from increased or prolonged RAG activity in leukemic lymphoid blasts.…”
Section: Discussionmentioning
confidence: 99%
“…Other models have suggested that some genomic regions may be particularly susceptible to breakage (Wiemels et al, 2000). For example, a breakpoint microcluster within TEL was found close to a highly repetitive purine/pyrimidine repeat region that was prone to denature under physiological conditions (Thandla et al, 1999;Wiemels and Greaves, 1999). Similarly, scaffold attachment regions are associated with a subset of MLL translocation breakpoints (Broeker et al, 1996) and are believed to contain regions that become single-stranded under stress (Benham et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…ETV6 is located on band 12p13 which is genetically unstable and thus susceptible to chromosomal rearrangements [ 6 ]. In recent years ETV6 was shown to be involved in a variety of translocations associated with hematological malignancies of both myeloid as well as lymphoid origin [ 1 , 7 ]. The diversity of ETV6 rearrangements is striking considering that the breakpoints do not cluster within a particular region of the gene [ 4 ].…”
Section: Introductionmentioning
confidence: 99%